Focusing on Sodium Glucose Cotransporter-2 and the Sympathetic Nervous System: Potential Impact in Diabetic Retinopathy - Lakshini Y. Herat; Vance B. Matthews; P. Elizabeth Rakoczy; Revathy Carnagarin; Markus Schlaich (International Journal of Endocrinology)
The prevalence of diabetes is at pandemic levels in today’s society. Microvascular complications in organs including the eye are commonly observed in human diabetic subjects. Diabetic retinopathy (DR) is a prominent microvascular complication observed in many diabetics and is particularly debilitating as it may result in impaired or complete vision loss. In addition, DR is extremely costly for the patient and financially impacts the economy as a range of drug-related therapies and laser treatment may be essential. Prevention of microvascular complications is the major treatment goal of current therapeutic approaches; however, these therapies appear insufficient. Presently, sodium glucose cotransporter-2 (SGLT2) inhibitors may offer a novel therapy beyond simple glucose lowering. Excitingly, the EMPA-REG clinical trial, which focuses on the clinically used SGLT2 inhibitor empagliflozin, has been extremely fruitful and has highlighted beneficial cardiovascular and renal outcomes. The effects of SGLT2 inhibitors on DR are currently a topic of much research as outlined in the current review, but future studies are urgently needed to fully gain mechanistic insights. Here, we summarize current evidence and identify gaps that need to be addressed.